THE PROCESS OF WASTEWATER TREATMENT BY PHYSICAL-CHEMICAL METHODS - Salohiddinov Fayzulloh Fazliddin o’g’li (European Science Publishing, 2024)
Wastewater treatment through physical-chemical methods stands as a cornerstone in the preservation of environmental integrity and public health. This abstract provides a concise overview of the process, elucidating its key components and objectives. Beginning with coagulation and flocculation, wherein chemical agents induce the aggregation of contaminants, the process progresses to sedimentation, filtration, and adsorption, each stage targeting specific pollutants for removal. Finally, disinfection ensures the elimination of harmful microorganisms, rendering the treated water safe for discharge or reuse. Through a synergistic combination of physical and chemical mechanisms, wastewater treatment embodies a vital nexus of science, engineering, and environmental stewardship, safeguarding water resources for present and future generations.